2005
DOI: 10.3748/wjg.v11.i28.4447
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis caused by leptospirosis: Report of two cases

Abstract: Two cases of acute pancreatitis with leptospirosis are reported in this article. CASE 1: A 68-year-old woman, presented initially with abdominal pain, nausea, vomiting, and jaundice. She was in poor general condition, and had acute abdominal signs and symptoms on physical examination. Emergency laparotomy was performed, acute pancreatitis and leptospirosis were diagnosed on the basis of surgical findings and serological tests. The patient died on postoperative d 6. CASE 2: A 62-year-old man, presented with fev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 13 publications
(13 reference statements)
0
28
1
1
Order By: Relevance
“…In most series published in the English literature, gallstones are the leading cause, followed by alcohol. Although the reported figures vary, the frequencies of metabolic and infectious causes in the present series are higher than those reported [4,8,11,12] . Idiopathic AP includes cases with unelucidated etiology.…”
Section: Discussioncontrasting
confidence: 54%
“…In most series published in the English literature, gallstones are the leading cause, followed by alcohol. Although the reported figures vary, the frequencies of metabolic and infectious causes in the present series are higher than those reported [4,8,11,12] . Idiopathic AP includes cases with unelucidated etiology.…”
Section: Discussioncontrasting
confidence: 54%
“…2 Pancreatitis is described as an uncommon complication of leptospirosis, but there are a considerable number of reports in literature. [37][38][39][40] In the present study, the complications found were pulmonary bleeding (14%), tract intestinal bleeding (13%), atrial fibrillation (11.4%), pulmonary infection (6.0%), meningitis (1.0%) and pancreatitis (0.5%).…”
Section: Discussionmentioning
confidence: 99%
“…An immunological basis for pathogenesis of leptospirosis including Toll like receptor (TLR) 2 activation is described recently [12]. The most consistent pathologic finding in leptospirosis is vasculitis of capillaries manifested by endothelial oedema, necrosis and lymphocytic infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The most consistent pathologic finding in leptospirosis is vasculitis of capillaries manifested by endothelial oedema, necrosis and lymphocytic infiltration. Small vessel vasculitis and ischemic injury leading to activation of proteolytic enzymes and auto-digestion is a possible mechanism [12]. All the patients described in the current series, were hemodynamicaly unstable at presentation or within the first 24 h of hospital stay.…”
Section: Discussionmentioning
confidence: 99%